The Effect of Macroeconomic Fundamentals on the Financial Performance with Deposits as Intervening Variables: A Case Study of Sharia Banks in Indonesia - Sri Hermuningsih (Universitas Proklamasi 45 Yogyakarta, 2019)
The aim of this research is to determine the effect of macroeconomic funda-mentals on financial performance with deposits as intervening variables in sharia banking in Indonesia. The research of macroeconomic fundamentals in the banking sector is an important component for improving the bank's financial performance. The research samples were all sharia public banks of year 2014 until 2017. By using purposive sampling method, data analysis in this research applied Partial Least Square. The results of this research indicated that macroeconomic fundamentals and deposits have a positive effect on financial performance. The results of the study have some implications for policies which can help to improve the performance of the sharia banking sector.